Ultra-high efficiency bremsstrahlung production in the interaction of direct laser-accelerated electrons with high-Z material - Tavana, P.; Bukharskii, N.; Gyrdymov, M.; Spillmann, U.; Zähter, Ş.; Cikhardt, J.; Borisenko, N. G.; Korneev, Ph.; Jacoby, J.; Spielmann, C.; Andreev, N. E.; Günther, M. M.; et al. (Frontiers in Physics, 2023)
In this work, we present a highly efficient approach to generate an ultra-high flux, high-energy Bremsstrahlung in interaction of direct laser accelerated (DLA) electrons with a several millimeters thick high-Z converter. Directed beam of DLA electrons with energies up to \SI{100}{\MeV} was produced in the interaction of sub-ps laser pulse of moderate relativistic intensity with long-scale plasma of near-critical density obtained by irradiation of low-density polymer foam with a ns laser pulse. In the experiment, tantalum isotopes generated via photonuclear reactions with threshold energies above \SI{40}{\MeV} were observed. Geant4 Monte Carlo code, with the measured electron energy and angular distribution as input parameters, was used to characterize the Bremsstrahlung spectrum responsible for the registered yields of isotopes from \ce{^{180}Ta} to \ce{^{175}Ta}. It is shown that when the DLA electrons interact with tantalum converter, the directed Bremsstrahlung with an average photon energy of \SI{18}{\MeV} and $\sim 2 \cdot 10^{11}$ photons per laser shot in the energy range of giant dipole resonance (GDR) and beyond ($\geq$ \SI{7.5}{\MeV}) is produced. This results in an ultra-high photon flux of $\sim\SI{6e22}{\steradian^{-1}\s^{-1}}$ and a record conversion efficiency of \SI{2}{\%} of the focused laser energy into high-energy Bremsstrahlung.